2003
DOI: 10.1080/14660820310016084
|View full text |Cite
|
Sign up to set email alerts
|

Paradigms for the identification of new genes in motor neuron degeneration

Abstract: It is estimated that between 10-20% of amyotrophic lateral sclerosis (ALS) is familial and these cases encompass recessive and dominant modes of inheritance. So far, mutations in three genes, superoxide dismutase 1 (SOD1), the p150 subunit of dynactin (DCTN1), and alsin have been shown to be directly causal for motor neuron degeneration in humans. However, clearly the disorder is genetically heterogeneous and other causal genes remain to be found that explain the vast majority of familial ALS cases. Human gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Axonal transport is essential for neuronal function and survival (Goldstein, 2003;Hafezparast et al, 2003;Holzbaur, 2004). In Drosophila motoneurons the BMP pathway is activated at the synaptic terminal but ultimately results in regulation of transcription in the nucleus (Ball et al, 2010;Kim and Marqués, 2010), thus this signaling pathway is dependent on long-range signal propagation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axonal transport is essential for neuronal function and survival (Goldstein, 2003;Hafezparast et al, 2003;Holzbaur, 2004). In Drosophila motoneurons the BMP pathway is activated at the synaptic terminal but ultimately results in regulation of transcription in the nucleus (Ball et al, 2010;Kim and Marqués, 2010), thus this signaling pathway is dependent on long-range signal propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Blockages in axonal transport result in death of the neuron and, if widespread, nervous system disorders (Goldstein, 2003). Errors in retrograde transport have been shown to cause neuron degeneration in diseases such as motor neuron disease, amyotrophic lateral sclerosis, and spinal muscle atrophy (Hafezparast et al, 2003;Levy et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The most recognized impairments and their measures include mutations to cargos (Meyer and Potter 1995;Wong, He et al 2000) and molecular motor cargo carriers (Hafezparast, Ahmad-Annuar et al 2003;Teuchert, Fischer et al 2006;Mitchell and Lee, 2009) that prevent the cargo from be appropriately bound to either dynein or kinesin. Other deficits include correlations to energetics, such as decreased mitochondrial transport or a decrease in overall transport due to a drop in mitochondrial potential (Ackerley, Grierson et al 2004).…”
Section: Category Definitionsmentioning
confidence: 99%
“…Recent evidence suggests that the tail region of dynein, through its subunits or associated proteins, controls its own motor activity. In vitro studies found that the legs at odd angles (Loa) mutation F580Y in the tail of the cytoplasmic dynein heavy chain (Hafezparast et al, 2003) inhibits motor processivity (Ori-McKenney et al, 2010). In addition, dynein-associated protein NudE (NDE1) and Lis1 are involved in the interaction between the tail and motor domains of dynein (OriMcKenney et al, 2010;Zylkiewicz et al, 2011).…”
Section: Box 2 Intramolecular Motor-tail Communicationmentioning
confidence: 99%